1997
DOI: 10.1093/emboj/16.9.2171
|View full text |Cite
|
Sign up to set email alerts
|

Function of the Greek key connection analysed using circular permutants of superoxide dismutase

Abstract: Human Cu,Zn superoxide dismutase (SOD) is a single domain all beta-sheet protein with its eight beta-strands arranged as a Greek key beta-barrel or immunoglobulin fold. Three circularly permuted variants of SOD were made by joining the native amino- and carboxy-termini, and introducing new termini at sites originally within connections between beta-strands. The locations of the new termini were chosen to interrupt beta-turns between the two N-terminal beta-hairpins and the short cross-barrel Greek key connecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…Fully metallated SOD1 was delipidated using hydroxyalkoxypropyl dextran type III (Sigma-Aldrich) as described previously (19) before de-metallation. Metal-deficient apo-enzymes were prepared as described previously (23), and loss of enzyme activity was confirmed after de-metallation. The metal content of purified enzymes was estimated as described previously (22).…”
Section: Methodsmentioning
confidence: 99%
“…Fully metallated SOD1 was delipidated using hydroxyalkoxypropyl dextran type III (Sigma-Aldrich) as described previously (19) before de-metallation. Metal-deficient apo-enzymes were prepared as described previously (23), and loss of enzyme activity was confirmed after de-metallation. The metal content of purified enzymes was estimated as described previously (22).…”
Section: Methodsmentioning
confidence: 99%
“…The reaction was allowed to proceed at Ϫ5-0°C for 1 h. After cleavage, the peptides were dissolved in 50% acetonitrile, 0.1% trifluoroacetic acid and lyophilized. The crude, reduced peptides were purified using preparative reverse-phase HPLC (RP-HPLC) 1 on a Vydac C18 column. Gradients of 0.1% aqueous trifluoroacetic acid and 90% acetonitrile, 0.09% trifluoroacetic acid were employed with a flow rate of 8 ml/min, and the eluant was monitored at 230 nm.…”
Section: Methodsmentioning
confidence: 99%
“…It may be thought of as joining the ends of a protein and then opening the chain elsewhere. These experiments have shown that it is possible in some cases to permute the termini of a protein and still allow folding into the native conformation (1,2), thus providing valuable information on protein folding. In practice the conceptual "circular proteins" intrinsic to the design of circular permutants are never actually synthesized but are theoretical intermediates.…”
mentioning
confidence: 99%
“…Alkylated and separated EC-SOD monomers were sequentially dialyzed against 50 mM acetate͞10 mM EDTA, pH 3.8; 50 mM acetate͞100 mM NaCl, pH 3.8; 100 mM acetate, pH 3.8; 100 mM acetate, pH 5.5; 100 mM acetate͞50 M CuSO 4 ͞20 M ZnSO 4 , pH 5.5; and 10 mM Tris-HCl, pH 7.4 as described (20,21).…”
mentioning
confidence: 99%